Faktor yang Berhubungan dengan Pengetahuan Ibu Hamil tentang Deteksi Risiko Tinggi Kehamilan - Alvionita, Vinny; Erviany, Nunung; Angraini, Rini; Nurfitri, Nurfitri; Ramadhani, Andini Aulia (Jurnal Sehat Mandiri, 2023)
Background: High-risk pregnancy is a major factor in increasing the Maternal Mortality Rate(MMR) and Infant Mortality Rate(IMR) in Indonesia. It’s known high-risk early detection can be a planning solution for pregnancy and childbirth according to the level of risk, because knowledge has a relationship with high-risk pregnancies. The purpose of this study was to determine of level knowledge a pregnant women and analyze factors related to the knowledge of pregnant women about detecting high-risk pregnancies in the working area of Soppeng District Health Center. Method:Using a descriptive analytic research design approachcross-sectional and accidental sampling for techniques. The population in this study was 904 with of 90 sampel of pregnant women in area of Soppeng District(PHC of Batu-Batu, Cangadi, Cabenge, Sewo, Malaka and Takalala). Results:The distribution dominated of respondents was 20-35 years(81.1%), 3rd trimester gestational age(56.7%) and multigravid (67.8%), 38.9% had the SHS level, and 88.9% worked as hausewife. Of all the respondents 42.2% had good knowledge. Conclusion:The level of knowledge of pregnant women in area of Soppeng District Heatlh Center majority have well (42.2%). This is influenced by factors of age, education, work, age pregnancy and parity. Suggestion:It’s hoped that various parties will make efforts to prevent and promote health so as to reduce the number of high-risk pregnancies and other reproductive health problems.